MAPPER ALGORITHM AND IT’S APPLICATIONS - Sekuloski, Petar; Dimitrievska Ristovska, Vesna (Scientific Technical Union of Mechanical Engineering" Industry 4.0", 2019)
In this paper we analyze and apply one of the main algorithms of TDA (Topological Data Analysis), Mapper, on some real data sets. We use Mapper for visualization of a data sets, and we tend to get some insights if some key characteristics of the data are captured by the visualization and how they are connected with human perception of the data. Also, we will discuss if the visualization can make progress in further work.
Keywords: MAPPER ALGORITHM, TOPOLOGICAL DATA ANALYSIS, ALGEBRAIC TOPOLOGY, DATA SCIENCE, COMPUTATIONAL TOPOLOGY